Managing strategic intelligence techniques and technologies - Xu, M. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book focuses on environment information scanning and organization-wide support for strategic intelligence. It also provides practical guidance to organizations for developing effective approaches, mechanisms, and systems to scan, refine, and support strategic information provision"--Provided by publisher.